Effects of sand size on spread and heat transfer of continuous spill fires with small leakage rates - Song, Jia; Luo, Ning; Li, Haihang; Liu, Jiahao (Journal of thermal analysis and calorimetry, 2024)
Spill fire, a kind of common fire accident, has the characteristics of strong sudden occurrence and fast spread rate, so there has been widespread concern about it. Compared with pool fire, there is limited research on spill fires now. In order to study the process of fire spread and combustion on sand substrate, a series of experiments were designed to investigate the effect of sand particle size on the spread and heat transfer of the continuous ethanol spill fire. The flame spread distance, substrate temperature, and penetrating heat radiation were measured. The resistance effect of sand, spread distance and rate, and steady linear burning rate were analyzed. Moreover, heat loss was also calculated. The results show that sand can effectively impede the development of spill fire. On the one hand, dry sand has strong capillary action, which makes most of the fuel adsorbed upward by the sand layer after entering the flow trough. Therefore, sand has obstructive capacity on the spread of liquid fuel, thereby shortening the spread distance of spill fire. On the other hand, sand has strong thermal conductivity, which can reduce the stable burning area of spill fire by increasing the total thermal feedback of spill fire and improving the steady burning rate of fuel. However, if the particle size of sand is too small, the liquid fuel will spill from the sand surface. In this case, the resistance effect of sand on the spread of liquid fuel will weaken. Therefore, sand with appropriate particle size should be selected for spill fire in practice.